PERAN ARBITRASE SYARIAH DALAM MENYELESAIKAN SENGKETA PEMBIAYAAN BERDASARKAN AKAD MUDHARABAH - Ukhtun Fajrotin (Al-Amwal : Journal of Islamic Economic Law, 2021)
AbstractThe development of the business world is getting more advanced, in the current era it has resulted in an increase in disputes that occur among business people. Business people prefer non-litigation channels such as sharia arbitration. Arbitration is a court of peace, where the parties to a dispute or dispute want their dispute over personal rights that they can fully control. Includes settlement of mudharabah financing contract disputes at Islamic Banks. In this article, it discusses how sharia arbitration is in resolving disputes and how to settle financing disputes based on the mudharabah contract. This research uses a descriptive qualitative approach. This type of research is a literature review method  and uses a normative approach and a juridical approach. In the results of this study, sharia arbitration in dispute resolution must determine a contract in advance to determine whether the dispute will be resolved in a religious court or arbitration. If there is no clear agreement at the beginning to determine the place for dispute resolution, it will be difficult for both parties who have debts and parties who have receivables. Meanwhile, solving the problem with the financing of the mudharabah contract, here the financing contract is signed by the parties before a dispute occurs and to anticipate the methods for resolving the dispute however, that most important thing is the content of the mudharabah contract financing it self.